KINERJA KELOMPOK TANI DALAM MENUNJANG PENDAPATAN USAHATANI PADI SAWAH DI DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Irawati,M.R.Yantu, Eni (AGROTEKBIS, 2015)
The aims of this study is to analyze the performance of farmer institutional, farm income of rice wetland, and the form of relationship between performance of farmer institutional and income of rice wetlandin Sidera Village,Sigi Biromaru Subdistrict, Sigi Regency. The research location was determined by purposively. It was selected because Sidera Village has most of farmer institutional in Sigi Biromaru Subdistrict. Population in this study is farmer institutional in Sidera Village which consist of14 members of farmer institutional.All of them were done samples. From each farmer institutionalwas taken 10 percent respondents by simple random sampling technique. There are 39 respondents were interviewed. The result of analysis showed that the score percentage of performance for farmer institutionalis 70,65percent. The score indicatesthat the farmer institutional in high criteria. On the other side,income of rice field is Rp 11.096.116,88 for one hectar of one season. The form of relationship between performance of farmer institutional and income of rice field in Sidera Village is positif and significants at level of ? 1 percent.